2014
DOI: 10.1515/hmbci-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol regulates insulin signaling and inflammation in adipose tissue

Abstract: Background Obesity-associated low-grade inflammation at white adipose tissue (WAT) leads to metabolic defects. Sex steroid hormone estrogen may be protective against high-fat diet (HFD)-induced obesity and insulin resistance. This has been tested by many previous studies utilizing rodent models of ovariectomy (OVX) and/or treatment of estradiol (E2), the major biologically active form of estrogen. Body weight and adiposity are increased by OVX and reduced following E2 treatment however. Thus, the protective ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
3
26
0
2
Order By: Relevance
“…In the present study we used female mice because they are more resistant to diet-induced metabolic changes [7]. The female sex hormones are thought to be protective against metabolic syndrome and low-grade inflammation [8, 45, 46]. In humans, there are fewer incidents of obesity-related metabolic disorders prior to menopause in women [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we used female mice because they are more resistant to diet-induced metabolic changes [7]. The female sex hormones are thought to be protective against metabolic syndrome and low-grade inflammation [8, 45, 46]. In humans, there are fewer incidents of obesity-related metabolic disorders prior to menopause in women [47].…”
Section: Discussionmentioning
confidence: 99%
“…The protection against the development of liver cancer in carcinogen-treated mice also depends on ERα-mediated estrogen signaling of forkhead box protein A (Foxa) factors such as Foxa1 and Foxa2 [101] pioneer transcription factors in the liver, crucial for steroid hormone signalling (estrogens and androgens) as essential controllers of variations of liver cancer in terms of gender [95]. The integrative genomic analysis showed that the risk of HCC in women might be associated with the SERPINA6-rs1998056 regulated by FOXA/ERα [102].…”
Section: Relationship Between Estrogens/ers and Hbv-related Acute LIVmentioning
confidence: 99%
“…Recently, we demonstrated that HCR rats are protected from early development (i.e., ϳ11 wk postsurgery) of OVX-induced IR assessed by homeostatic model assessment of insulin resistance (HOMA-IR) (47) and found that, unlike HCR rats, LCR rats had an exaggerated insulin response to a glucose tolerance test. Additionally, white (WAT) and brown adipose tissues (BAT) are gaining appreciation as also being important tissues in whole body glucose regulation (26) and may influence changes in glucose metabolism associated with both loss of ovarian hormones (39) and low aerobic capacity (44). It is known that ovary-intact female HCR rats display 30 -50% greater insulin-induced glucose uptake and oxidation in skeletal muscle compared with LCR rats (35).…”
mentioning
confidence: 99%